(untitled) (Madhyabindu Journal, 2026)
Traditional approaches to teaching have been gradually shifted with new approaches. Teacher and textbook-centred teaching strategies, methods and approaches are not equally beneficial in education to engage all learners actively in the learning process. This context reveals the need of shifting in our pedagogical practices. Transformative pedagogical approaches focus on personalized and students- centered strategies of teaching, which are alternative pedagogies to traditional ones. In this context, this paper examines the problems of using traditional pedagogical approaches and the need for transformative pedagogical approaches in education. Particularly, it examines the context of using traditional approaches and the limitations, the ubiquitous need for pedagogical shifting, and the relevance of transformative pedagogies for supporting students’ learning. To explore the issue, we reviewed journal articles, conference papers, books, and book chapters. We derived the findings of the study as we interpreted how it is essential to intervene in traditional pedagogical approaches, since they could not provide equal opportunities and benefits of education to the diverse learners. Neither did they create a collaborative and creative learning platform. To address the diverse needs and interests of learners, traditional approaches need to be shifted with transformative approaches of teaching. As our education system is also not yielding fruitful result producing creative, skill-oriented and critical citizens. Although the relevance of transformative pedagogies has been realized, the foundational preparation and readiness for their implementations are awaited. Further studies need to explore how transformative pedagogies can be executed in our classrooms effectively.